Spigolature stenbeckiane - Moscadelli, Stefano (L'ospite ingrato, 2024)
In the context of the attention received by Steinbeck’s works between in the late 1930s and early 1940s, that towards The Moon is down/Nuits sans lune stands out. Already circulated in a first London edition (Notte senza luna, 1944) before its diffusion under the title La luna è tramontata, the text – strongly committed to supporting the partisan war – soon received a theatrical adaptation in Italy, which was widely commented by critics in the post-war period. Steinbeck’s success in Italy continued during the 1950s, when the writer visited Italy several times. Traces of these trips remain in the archives, especially the one in spring 1957 when Steinbeck, staying in Florence, met among others Bernard Berenson, to whom he later sent a letter of gratitude for the hospitality he had received. The letter is here for the first time fully published and contextualized.